Analysis of Coping Stress of Amil in Collecting Philanthropic Funds at Dompet Dhuafa Branch Offices in Indonesia - Armansyah Armansyah; Muhammad Ramadhan; Yenni Samri Juliati Nasution (CV. RADJA PUBLIKA, 2026)
Amil, as managers of zakat funds, play a strategic role in sustaining Islamic philanthropic governance. However, increasing fundraising targets, organizational uncertainty, and professional pressures expose amil to significant work stress. This study aims to examine the determinants of stress coping among amil at Dompet Dhuafa branch offices in Indonesia by integrating psychological coping theory with the maqāṣid al-sharī’ah framework. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 141 amil across branch offices in Indonesia. The model tested problem-focused coping, emotion-focused coping, and maqāṣid dimensions (Hifz al-din, Hifz al-nafs, and Hifz al-‘aql) as predictors of coping stress. The findings reveal that planful problem solving, seeking social support, positive reappraisal, accepting responsibility, self-controlling, and the maqāṣid dimensions significantly influence amil stress coping, while avoidance-based strategies such as distancing and escape avoidance are not significant. The results indicate that effective stress coping among amil is multidimensional, shaped by cognitive capacity, social support, and spiritual reinforcement within an institutional governance context. Theoretically, this study extends stress coping literature by empirically operationalizing maqāṣid al-sharī’ah as a coping determinant within Islamic philanthropic governance. Practically, the findings provide a foundation for zakat institutions to design integrated human resource policies that strengthen organizational support, cognitive resilience, and spiritual values to ensure sustainable institutional performance.